Comparative study on nutritional quality and serum biochemical indices of common carp (Cyprinus carpio) aged from 11 to 23 months in the land-based container aquaculture system - Fangran Ma; Jintai Huang; Zhan Jin; Rui Feng; Lingran Wang; Chang Liu; Di Feng; Rui Shu; Meng Zhang; Miao Yu; Hongxia Jiang; Zhigang Qiao; et al. (Aquaculture Reports)
To reveal the effects of recirculating aquaculture modes on the muscle quality of common carp, the impacts of land-based containers recirculating aquaculture system (C-RAS) and traditional pond system (TP) on the physical properties, nutrient composition, mineral elements, and volatile substances of common carp were analyzed in this experiment. The results showed that dripping, storage, and frozen loss were significantly lower in C-RAS than in TP, while the cooked meat rate was significantly higher than in the TP (P<0.05). The moisture and crude fat contents of C-RAS were significantly lower than those of TP (P<0.05), and the crude protein content, Saturated fatty acids, polyunsaturated fatty acids, C20:5n-3, C22:6n-3, and ω-3 fatty acids were significantly higher than those of TP (P<0.01); C-RAS had significantly higher levels of essential amino acids and non-essential amino acids than TP (P<0.05). The experiment showed the muscle nutritional quality of common carp cultured in C-RAS was better. The results provide references for future regulation of quality and nutrition for muscle of fish cultured through recirculating aquaculture modes.